Decrease in naturally occurring antibodies against epitopes of Alzheimer’s disease (AD) risk gene products is associated with cognitive decline in AD - Gu, Dongmei; Wang, Luchun; Zhang, Nan; Wang, Huali; Yu, Xin (Journal of neuroinflammation, 2023)
Naturally occurring antibodies (NAbs) are germline-encoded immunoglobulins that can bind to and clear out self-neo-epitopes as well as apoptotic and necrotic cells. However, NAbs pathological relevance in Alzheimer's disease (AD) is not well-understood. Twenty-eight candidate proteins encoded by AD-associated genes were selected for this study based on a number of selection criteria, including preferential expression in the brain and B-lymphocyte cells. The levels of NAbs in plasma were analyzed according to their epitopes in age- and gender-matched cognitively normal subjects (CN, n = 56), subjects with mild cognitive impairment (MCI, n = 16) and subjects with AD (n = 56). We aimed to study the levels of their NAbs in plasma and their associations with cognitive decline in individuals with AD. Of the 28 antigens tested, 17 showed decreased NAbs in individuals with AD; in particular, NAb-TREM2 had an area under the ROC curve of 0.806, with the highest sensitivity (0.370) at 95% specificity among all 28 tests. Further protein-protein interaction networks and functional enrichment analysis suggested that target genes were enriched in AD-related pathological processes classified under "Alzheimer's disease", "neurodegenerative disease" and "amyloidosis". The "Alzheimer's disease" and "neurodegenerative disease" clusters, which converged on the initial "recognition" step of microglial phagocytosis, showed the best diagnostic performance for AD. This study suggests a decline in the function of the adaptive immune system in AD, and the levels of circulating NAbs are likely to serve as biomarkers for surveilling the progression of AD.